Survey of the bryophytes of a gallery forest in the National Park of Serra do Cipó, Minas Gerais, Brazil - Ronaldo Viveiros de Sousa; Paulo Eduardo Aguiar Saraiva Câmara (Acta Botânica Brasílica, 2015)
Serra do Cipó has attracted the interest of many researchers over the years because of its unique characteristics, particularly the fact that the site represents the transition between Cerrado and Atlantic Forest. The study area of Serra do Cipó is located along a gallery forest "córrego Três Pontinhas," at 19°16'00" S and 43°32'49" W and an altitude of 1,188 m. The objective of this study was to survey the Division Bryophyta in a gallery forest within the National Park of Serra do Cipo, Minas Gerais. Collections were made during the months of November 2009 and July 2011. We found 15 families, 26 genera, 43 species, and 4 varieties of mosses. The families with the largest number of species were Leucobryaceae (10), Sematophyllaceae (9), and Calymperaceae (6). Other families included Fissidentaceae (3), Bryaceae, Pylaisiadelphaceae, Pottiaceae, and Orthotrichaceae (2 spp. each); Brachytheciaceae, Cryphaeaceae, Fabroniaceae, Helicophyllaceae, Hypnaceae, Polytrichaceae, and Sphagnaceae had only 1 sp. each. Three new records for the state of Minas Gerais were found: Acroporium caespitosum, A. longirostre, and Colobodontium vulpinum.